RCAN1 Knockdown Reverts Defects in the Number of Calcium-Induced Exocytotic Events in a Cellular Model of Down Syndrome - Vásquez-Navarrete, Jacqueline; Martínez, Agustín D.; Ory, Stéphane; Baéz-Matus, Ximena; González-Jamett, Arlek M.; Brauchi, Sebastián; Caviedes, Pablo; Cárdenas, Ana M. (Frontiers in Cellular Neuroscience, 2018)
In humans, Down Syndrome (DS) is a condition caused by partial or full trisomy of chromosome 21. Genes present in the DS critical region can result in excess gene dosage, which at least partially can account for DS phenotype. Although regulator of calcineurin 1 (RCAN1) belongs to this region and its ectopic overexpression in neurons impairs transmitter release, synaptic plasticity, learning and memory, the relative contribution of RCAN1 in a context of DS has yet to be clarified. In the present work, we utilized an in vitro model of DS, the CTb neuronal cell line derived from the brain cortex of a trisomy 16 (Ts16) fetal mouse, which reportedly exhibits acetylcholine release impairments compared to CNh cells (a neuronal cell line established from a normal littermate). We analyzed single exocytotic events by using total internal reflection fluorescence microscopy (TIRFM) and the vesicular acetylcholine transporter fused to the pH-sensitive green fluorescent protein (VAChT-pHluorin) as a reporter. Our analyses showed that, compared with control CNh cells, the trisomic CTb cells overexpress RCAN1, and they display a reduced number of Ca2+-induced exocytotic events. Remarkably, RCAN1 knockdown increases the extent of exocytosis at levels comparable to those of CNh cells. These results support a critical contribution of RCAN1 to the exocytosis process in the trisomic condition.